The effect of lanthanum addition on the microstructure and mechanical properties of Mg-modified hydroxyapatite ceramics - (:unkn) unknown (UNIV NOVI SAD, FAC TECHNOLOGY, 2021)
In the present paper, the effect of La2O3 (0.25, 0.5 and 1 wt.%) addition on the phase stability, porosity, density, hardness, fracture toughness, compressive strength and brittleness index of hydroxyapatite modified with 1 wt.% of MgO was investigated. Hydroxyapatite (HA) without additives sintered at 1300 degrees C has mixture of dominant hydroxyapatite phase with beta-tricalcium phosphate (beta-TCP), alpha-tricalcium phosphate (alpha-TCP) and calcium oxide (CaO) phases. The microstructure is characterized with transgranular microcracks and oversized grains. Although the density and hardness of the pure HA increased with increasing temperature, a steady decrease in fracture toughness (from 0.96 to 0.71 MPa.m(1/2)) and compressive strength (from 130.2 to 65.6 MPa) was observed. For the HA modified with 1 wt.% of MgO the highest compressive strength (183.2 MPa) and fracture toughness (1.47 MPa.m(1/2)) were obtained at 1200 degrees C and at this temperature the brittleness index was 3.24 mu m(-1/2). Increase in the sintering temperature led to the increase of the brittleness index of the pure HA, MgO modified HA and La2O3-MgO modified HA samples. The addition of 1 wt.% La2O3 to 1 wt.% MgO-HA contributed to the increase in the compressive strength of about 10% (from 183.2 to 202.0 MPa), fracture toughness of about 69% (from 1.37 to 2.32 MPa.m(1/2)) and also decrease of the brittleness index from 3.24 to 2.18 mu m(-1/2). The best performance after sintering at 1300 degrees C was obtained for the MgO-HA sample with 0.25 wt.% La2O3. As a result of this study, a new candidate material for biomedical application with superior mechanical properties and the phases that do not cause adverse reactions in the human body could be 1 wt.% MgO-HA modified with 1 wt.% La2O3 and sintered at 1200 degrees C.
Keywords: hydroxyapatite; magnesium oxide; lanthanum oxide; sintering; mechanical properties; MAGNESIUM-OXIDE; BIOLOGICAL-PROPERTIES; TRICALCIUM PHOSPHATE; CALCIUM PHOSPHATES; FRACTURE-TOUGHNESS; SINTERING BEHAVIOR; BONE SUBSTITUTE; COMPOSITES; POWDER; STRENGTH